Surgical correction of anomalous origin of right pulmonary artery from aorta in a four day old neonate. Issue 1 (July 1986) - Sibley, Y D; Roberts, K D; Silove, E D
Abstract : A two day old neonate presented with cyanosis. The echocardiogram was misinterpreted as showing transposition of the great arteries. Cardiac catheterisation was performed the next day and showed anomalous origin of the right pulmonary artery from the aorta. Surgical correction at the age of 4 days was successful. At the age of nine months the patient was symptom free with "normal" cardiac anatomy. This patient is the youngest case to have successful correction of this anomaly. The initial misinterpretation of the echocardiogram could have had serious consequences if balloon atrial septostomy had been attempted.